IMPROVING SPEAKING ABILITY THROUGH SMALL GROUPS DISCUSSION FOR THE EIGHTH YEAR STUDENTS OF SMPN 2 SALUPUTTI IN TANA TORAJA - Roni La’biran (Elite : English and Literature Journal, 2017)
AbstractThe objective of the study is to know the small groups discussion can improve the students’ speaking ability. In order to achieve the objective of this study, the writer designed an experimental method using pre-test and post- test. The population of this study was the eighth year students of Junior High School of SMPN 2 Saluputti. The sample of this study was the eight year students in academic year 2015/2016. The number of the students was 16 students. There were four meetings during the experiment. Before the experiment was conducted, the students were given a pre-test. At the end of the experiment, the students were given a post- test. The result of this study revealed that, the post- test scores were better than the pre-test scores. It could be seen by comparing their means. The mean score of the pre-test was 22.8, while the mean of the post test was 78.2. It shows that the mean score of the post test is greater than the pre test. The difference between pre test and post test was 55.3. In line with the result, the writer concludes that the Small Groups Discussion strategy is one of the effective strategies as to increase the activity and student learning outcomes in speaking subject. In teaching and learning activities teachers are expected to make cooperative learning as an alternative type of Small Groups Discussion in speaking subject to increase the activity and student learning outcomes, especially when teaching speaking to eighth year students of junior high school. AbstrakTujuan dari penelitian ini adalah untuk mengetahui apakah Diskusi Kelompok Kecil dapat meningkatkan kemampuan berbicara siswa. Untuk mencapai tujuan penelitian ini, penulis merancang metode eksperimen dengan menggunakan pre-test dan post-test. Populasi penelitian ini adalah siswa kelas VIII SMPN 2 Saluputti. Sampel penelitian ini adalah delapan tahun siswa pada tahun ajaran 2015/2016. Jumlah siswa adalah 16 siswa. Ada empat pertemuan selama percobaan. Sebelum percobaan dilakukan, siswa diberi pre-test. Pada akhir percobaan, siswa diberi post-tes. Hasil penelitian ini menunjukkan bahwa nilai post-test lebih baik daripada nilai pre-test. Skor rata-rata pre-test adalah 22,8, sedangkan dari post test adalah 78,2. Ini menunjukkan bahwa nilai rata-rata post test lebih besar daripada pre test. Perbedaan antara pre test dan post test adalah 55,3. Sejalan dengan hasilnya, penulis berkesimpulan bahwa strategi Diskusi Kelompok Kecil merupakan salah satu strategi efektif untuk meningkatkan aktivitas dan hasil belajar siswa dalam mata pelajaran berbicara. Dalam kegiatan belajar mengajar guru diharapkan dapat melakukan pembelajaran kooperatif sebagai alternatif jenis Diskusi Kelompok Kecil dalam berbicara yang dapat meningkatkan aktivitas dan hasil belajar siswa, terutama saat mengajar berbicara kepada siswa kelas VIII SMP.